ON THE OCCURRENCE OF A GIANT FLYING REPTILE (PTEROSAURIA) IN THE TERMINAL LATE CRETACEOUS OF THE LOWER VOLGA REGION - Averianov A.O.; Yarkov A.A. (My University, 2004)
A fragmentary proximal epiphysis of a humerus from the Campanian of the Polunino 2 locality (Volgograd Region) belongs to a giant pterosaur, Ornithocheiridae gen. et sp. indet. about 5 m in wingspread. Together with a second example from the Campanian of the eastern coast of the United States, the ornithocheirid from the Lower Volga Region is the latest representative of this group in the fossil record.
Keywords: Ornithocheiridae; Pterosauria; Campanian; Late Cretaceous; Volgograd Region; Russia; Mesozoic::Cretaceous::Upper::Campanian; Мезозой::Меловая::Верхний::Кампанский